Physico-Chemical Methods of Water Purification - Kushshaeva Marguba Rustam qizi (Zien Journals, 2023)
The article describes the methods of water purification. About desalination and desalination of water by distillation, physico-chemical bases of water purification by extraction, physico-chemical bases of water purification by evaporation.
Keywords: water; dryer; sun; economy